Performance evaluation of Iodine Deficiency Disorder control Program in Mandya District - Harish, Bekkalale Rudresh; Siddalingappa, Hugara; Kambale, Shambhulinga; Goud, Bhoompuram Nagaraja; Arulprakasam, Divya; Sannamadhu, Mythri; Marumada, Girish (Indian Journal of Community Health, 2021)
Background: Considering the burden of Iodine Deficiency Disorders in our country, Government of India has an exclusive national health program to prevent it from becoming a major public health concern. To attain its objectives, National Iodine Deficiency Disorder Control Program (NIDDCP) undertakes routine evaluation of the Program all over the country. Aim & Objective: To determine the prevalence of Goitre, to estimate Iodine content in salt samples and Iodine excretion in urine samples of schoolchildren aged between 6 to 12 years in Mandya district. Settings and Design: A cross sectional institutions based survey was conducted among schoolchildren from the villages in selected clusters of Mandya district. Materials and Methods: Probability Proportional to Size sampling method was used to select 30 clusters. 90 children aged between 6 to 12 years from each cluster were screened. Salt Iodine content was ascertained by Iodometric titration method and urinary Iodine excretion was estimated by Sandell-Kolthoff method. Statistical analysis used: Frequency, proportions and mean were calculated and inferential statistics were used. Results: Prevalence of Goitre was 4.4%, with higher prevalence among girls. 49.8% salt specimens lack adequate iodine (<15ppm) at household level. Median UIE was 164 Micrograms /litre. Conclusions: As per the impact indicators, IDD is not a public health concern in Mandya district as of now.